COMMUNITY PARTICIPATION IN THE IMPLEMENTATION OF DEVELOPMENT IN MORELA VILLAGE, LEIHITU DISTRICT, CENTRAL MALUKU REGENCY - Sialana, Imran; Soselisa, Pieter S.; Rahanra, Ivonny Y. (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2024)
This research was conducted in Negeri Morella Village, Leihitu District, Central Maluku Regency, with the aim of identifying and describing community participation in the implementation of development in the area. The main focus of the research is to determine the extent of community participation in the development process and to identify the factors that support and hinder such participation. Data collection was carried out using a natural setting approach, utilizing primary data sources. The methods used included observation, interviews, and documentation. The results of the study indicate that community participation in development in Negeri Morella Village is still relatively low, particularly in the planning stages of development programs and activities. Nevertheless, the local government continues to involve the community in the implementation process. Interviews revealed that some community members are less active in participating, due to personal interests and social conditions. However, there are also community members who are quite active in contributing, especially in terms of labor. Despite this, some community members are less informed about the procedures for overseeing development. The factors influencing community participation include age, gender, education level, occupation, income, and environmental conditions. This research provides important insights into community participation in development in Negeri Morella Village, as well as the factors that influence it.